IMAGE-D3.2 - Final report on: Rock/fluid interactions at supercritical conditions - Ruggeri, Giovanni (Zenodo, 2015)
This report describes rock/fluid interactions at super-critical1 conditions buildingconcepts for deep fluid circulation and validation from lab results (Deliverable D3.2Rock/fluid interactions at supercritical conditions, pag. 14-15 of the DoW). In particular we report: • the results of fluid-rock interaction experiments by using a cold seal pressurevessel apparatus between aqueous solutions and crystalline solids in whichseveral parameters were taken into account, such as type of solid, fluidcomposition and its salinity, solid/fluid ratio, P-T conditions. Fluids and solidswere characterized before and after experiments. • Fluid-rock interaction modelling by using the modified code-packages upgradedup to supercritical conditions. • Collection and geochemical/isotopic analyses of fluid samples from geothermalsystems in Iceland. • Validation of fluid-rock interaction modelling by comparing the results with thedata of fluid from active geothermal fields. • Data interpretation and assessment of the mineralogical and chemical changesof the rocks and fluids by fluid-rock interaction of magmatic hydrothermalsystem around cooling intrusions at supercritical conditions as a function oftemperature, pressure and fluid composition. FP7